Optimizing Compliance: Comparative Study of Data Laws and Privacy Frameworks Extended Abstract - Rocha, Lucas Dalle; Canedo, Edna Dias (Anais Estendidos do Congresso Brasileiro de Software: Teoria e Prática (CBSoft); 2025: Anais Estendidos do XVI Congresso Brasileiro de Software: Teoria e Prática, 2025)
The study explores challenges in complying with multiple data privacy laws with a Systematic Literature Review (SLR), assessing similarities and differences among them. After validation through a survey, findings highlighted a lack of theoretical and practical knowledge about Brazil’s General Data Protection Law (LGPD). Using Framework Analysis, we proposed a tool by correlating key legislative points and providing insights into data privacy compliance.